Monetary Policy Implementation : Operational Issues for Countries with Evolving Monetary Policy Frameworks - Maehle, Nils (IMF Working Papers; Working Paper ;, 2020)
This paper discusses operational issues for countries that want to reform their monetary policy frameworks. It argues that stabilizing short-term interest rates on a day-to-day basis has significant advantages, and thus that short-term interest rates, not reserve money, in most cases should be the daily operating target, including for countries relying on a money targeting policy strategy. The paper discusses how a policy formulation framework based on monetary aggregates can be combined with an operational framework that ensures more stable and predictable short-term rates to enhance policy transmission. It also discusses how to best configure an interest-rate-based operational framework when markets are underdeveloped and liqudity management capacity is weak.